THE CORRELATION BETWEEN MASTERING SIMPLE PRESENT TENSE AND THE STUDENTS’ ABILITY TO BUILD UP ADVERTISEMENT TEXT AT MAS NURUL HAKIM - Derliana Marbun (UIN Sumatera Utara, 2018)
The aim of this study is to know the significant correlation between mastering simple present tense and the students’ ability to build up advertisement text. This study was conducted on the first year students of MAS Nurul Hakim Tembung (2016). The population of this study was 46 students. In collecting data, I used test. The data was analyzed by product moment correlation. After analyzing the data, the writer finds that there is a significant correlation between mastering simple present tense and the students’ ability to build up advertisement text. It is known ∑ x = (3477), ∑ y= (2930), ∑ x = (280497), ∑ y = (202000), ∑ xy = (226460), the coefficient correlation is (0,3026). While rt (0,294) at ∝ =0,05. It means ro > rt (0,3026> 0,294). So, the hypothesis is accepted.Key Words: Mastering Simple Present Tense, to Build Up Advertisement Text.